Disciplined Open-Air Exercise to Decelerate Aging: Toward Ecstatic Pains - Nikkhah, Akbar (Journal of Aging Research And Healthcare, 2024)
This editorial aims to propose and delineate that disciplined open-air exercise can slow down aging in humans. The aging process may be slowed down by outdoor physical training (e.g., mountaineering, climbing, running, swimming, walking, jogging) mainly because of fresh air inhalation and psychological calmness. However, for outdoor exercise to be a healthy asset, it should be performed in unpolluted and uncontaminated environments. Advanced public education policies must be developed to persuade people to maximize their outdoor physical activities. This is to ensure achieving peace and serenity for both body and psych. Integrated social activities may also be encouraged with open-air exercise. As such, stress in the third millennium can be pragmatically attenuated and managed. As a result of slower aging process, human life quality may improve worldwide.
Keywords: Open-air exercise; aging; physiology; science; human; life quality